Application of Educational Technology and Teachers' Competence in Improving Teaching Effectiveness in Islamic Education Curriculum in Madrasah Aliyah in Indonesia - Supriandi, Supriandi; Haddar, Gamar Al; Saputri, Dwi Yuniasih; Halim, Chandra (The Eastasouth Journal of Learning and Educations, 2024)
This study investigates the application of educational technology and teacher competence in enhancing teaching effectiveness within the Islamic religious education curriculum at Madrasah Aliyah in Indonesia. Utilizing a quantitative analysis approach, data were collected from a sample of 180 respondents using a Likert scale ranging from 1 to 5. The data were analyzed with Structural Equation Modeling with Partial Least Squares (SEM-PLS 3). The findings reveal that the relationships between educational technology and teaching effectiveness (H1), teacher competence and teaching effectiveness (H2), as well as teaching effectiveness and the Islamic education curriculum (H3), are all positive and significant. These results underscore the critical role of both educational technology and teacher competence in improving teaching effectiveness, which in turn positively impacts the Islamic education curriculum. This study provides valuable insights for policymakers and educators aiming to enhance the quality of Islamic religious education through the strategic application of educational technology and the development of teacher competencies.